The two lines are said to be perpendicular if the product of thier slope is equal to the -1
The general equation of line:
![y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csobd57zth7rh9k4hz9amldzpq2owf0z4j.png)
where, m is the slope of the line
The given expression : y - 5 = -3(x -1 )
Simplify the expression:
![\begin{gathered} y-5=-3(x-1) \\ On\text{ comparing with the general form of line } \\ we\text{ get: m =(-3)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wzb0buhdbmg4pa83kuet0ytwbm5gbwbz7a.png)
Slope of the given line is m = (-3)
Let the slope of the second line is n
From the condition of the perpendicular lines
![\begin{gathered} \text{Slope of line1}* Slope\text{ of line 2= -1} \\ m* n=-1 \\ (-3)* n=-1 \\ n=(1)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qlyk2lohsendd0w1p07eh7lmbhelywvg9n.png)
Slope of the second line which is perpendicular to the given line is 1/3
Use the general form of equation of line to get the expression pf line2:
The passing points : (1,5)
![\begin{gathered} y-y_1=m(x-x_1) \\ y-5=(1)/(3)(x-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j2njhfkswvlzn0ji93xmei8nm4ucma8540.png)
The equation of line which is perpendicular to the line y-5=-3(x-1) is y - 5 = 1/3 (x - 1 )
Answer : y - 5 = 1/3 (x - 1 )